Precipitation gradients drive high tree species turnover in the woodlands of eastern and southern Africa - Davies, Robert W.; Ryan, Casey M.; Harrison, Rhett D.; Dexte, Kyle G.; Ahrends, Antje; te Beest, Mariska; Benitez, Lorena; Brade, Thom K.; Carreiras, Joao M. B.; Druce, Dave J.; Fayolle, Adeline; Finckh, Manfred; et al. (Wiley, 2023)
Savannas cover one-fifth of the Earth’s surface, harbour substantial biodiversity, and provide a broad range of ecosystem ser-vices to hundreds of millions of people. The community composition of trees in tropical moist forests varies with climate, butwhether the same processes structure communities in disturbance-driven savannas remains relatively unknown. We investigatehow biodiversity is structured over large environmental and disturbance gradients in woodlands of eastern and southern Africa.We use tree inventory data from the Socio-Ecological Observatory for Studying African Woodlands (SEOSAW) network, cov-ering 755 ha in a total of 6780 plots across nine countries of eastern and southern Africa, to investigate how alpha, beta, andphylogenetic diversity varies across environmental and disturbance gradients. We find strong climate-richness patterns, withprecipitation playing a primary role in determining patterns of tree richness and high turnover across these savannas. Savannaswith greater rainfall contain more tree species, suggesting that low water availability places distributional limits on species,creating the observed climate-richness patterns. Both fire and herbivory have minimal effects on tree diversity, despite theirrole in determining savanna distribution and structure. High turnover of tree species, genera, and families is similar to turnoverin seasonally dry tropical forests of the Americas, suggesting this is a feature of semiarid tree floras. The greater richness andphylogenetic diversity of wetter plots shows that broad-scale ecological patterns apply to disturbance-driven savanna systems.High taxonomic turnover suggests that savannas from across the regional rainfall gradient should be protected if we are tomaximise the conservation of unique tree communities.
Keywords: Beta diversity; Climate-richness; Environmental gradients; Miombo; Phylogenetic diversity; Savanna; SDG-15: Life on land